IN VITRO AND IN SILICO STUDIES ON EVALUATING EREMANTHIN AS POTENTIAL THERAPEUTIC DRUG AGAINST BREAST CANCER - A, ANITA ROY; MARY, ANGEL; SABAPATHY, INDU; RAJALAKSHMI, MANIKKAM (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The present study was aimed to evaluate the anticancer property of eremanthin isolated from Costus speciosus against breast cancer using in vitro and in silico approaches and thereby to develop eremanthin as a typical phytotherapeutic drug against cancer. Methods: The presence of specific biologically active extract was confirmed under GC–MS/MS (gas chromatography–mass spectrometry) analysis. The cell proliferation inhibitory effect of the eremanthin was confirmed by MTT (3-(4,5-Dimethylthiazol-2-yl)-2,5-Diphenyltetrazolium Bromide) and LDH (lactate dehydrogenase) assay. In silico studies were performed to predict the targeted interaction of eremanthin with cancer proteins. Results: The GC–MS/MS analysis confirmed the presence of eremanthin with peak value of RA: 20.03. The MTT and LDH assays revealed the antiproliferative activity of eremanthin on MCF-7 and MDA-MB-231 breast cancer cell lines. The results provide stable interaction between eremanthin and cancer target proteins. Conclusion: Thus, the compound can be used as an effective herbal therapeutic molecule to treat cancer with further explorations.